Integrated Care of Atrial Fibrillation Using the ABC (Atrial fibrillation Better Care) Pathway Improves Clinical Outcomes in Chinese Population: An Analysis From the Chinese Atrial Fibrillation Registry - Yu-Feng Wang (Frontiers Media S.A., 2021)
Background: “Atrial fibrillation Better Care” (ABC) pathway has been proposed to improve the management of patients suffered from atrial fibrillation (AF). This integrated or holistic management approach comprise of three aspects, including “A” Avoid stroke or Anticoagulation; “B” Better symptom control with rate or rhythm control strategies; “C” Cardiovascular risk factor and Concomitant diseases management. We aimed to confirm the beneficial evidence of ABC pathway compliance in a Chinese AF cohort.Method and Results: From the Chinese Atrial Fibrillation registry (CAFR) dataset, a total of 19,187 non-valvular AF patients were enrolled, of which 4.365 (22.8%) were ABC pathway compliant (ABC compliance group). During a median follow-up of 4.1 ± 1.8 years, The incident rate of all-cause death in ABC compliance group and non-ABC compliance group is 2.7 and 1.1 per 100 person-year (p < 0.001), the incident rate of ischemic stroke is 1.3 and 0.8% per 100 person-year (p < 0.001), the incident rate of composite outcome, which consist of all-cause death, ischemic stroke and intracranial hemorrhage, is 3.8 and 1.9 per 100 person-year (p < 0.001). On Cox multivariable analysis, ABC pathway shows an independently association with reduction of all-cause death [hazard ratio (HR) = 0.82; 95% confidence interval (CI) = 0.70–0.95] and the composite outcome (HR 0.86, 95% CI 0.76–0.96). The increasingly components of ABC integrated care compliance is associated with lower risk of all-cause death and composite events.Conclusion: In a large cohort of Chinese AF patients, ABC pathway compliance shows an independently association with reduction of all-cause death and composite outcome of all-cause death, ischemic stroke and intracranial hemorrhage. Better compliance of ABC integrated care contributes to lower HR for adverse events.